-4x-4(1-2x)=7+4x

Simple and best practice solution for -4x-4(1-2x)=7+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-4(1-2x)=7+4x equation:


Simplifying
-4x + -4(1 + -2x) = 7 + 4x
-4x + (1 * -4 + -2x * -4) = 7 + 4x
-4x + (-4 + 8x) = 7 + 4x

Reorder the terms:
-4 + -4x + 8x = 7 + 4x

Combine like terms: -4x + 8x = 4x
-4 + 4x = 7 + 4x

Add '-4x' to each side of the equation.
-4 + 4x + -4x = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
-4 + 0 = 7 + 4x + -4x
-4 = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
-4 = 7 + 0
-4 = 7

Solving
-4 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 16x+5=10y | | (Q*0.33)+Q=72 | | 2(5y-7)+10=36 | | 4x+8-6x=7+6x-7 | | 150m-100m+38000=40400-150m | | 6=9/v | | 2g-4(2g-3)=-24 | | 2x+25=12x-10 | | -81=g-9 | | 4b^2-90=-2b | | 34y+237= | | 3y-5+2(y-5)=15+8y | | 1/2x-3(x-5)=5(x-9) | | 8(n-5)=-16 | | y-9=-1(x-0) | | x-4+2x+5=91 | | f/12 | | 1/3x-3(x-5)=5(x-9) | |  4-7x/2-2=x/8  | | A=2(6)(9)+2(10)(9)+(6)(10) | | (4x+9)+(3x-2)=28 | | 2s+3(5-2s)=47 | | 3x-(x-5)+6=x+9 | | 3n+16=4n+24 | | (6x+3)+(x+16)=180 | | Y=5(x+2)-2 | | 7.5+2.5x= | | 2x-9(x+8)=x+1 | | X+2x+4x=133 | | 2x-(8x+5)=8x-19 | | 3(x-2)-1=2 | | (X+7)2+20=0 |

Equations solver categories